Innovations in Aquaponics Technology and Building Sustainable Infrastructure for Agriculture - Ghaffar, Amna; Abbas, Aqsa; Afzal, Kinza; Batool, Kaneez; Nawaz, Binish; Zafar, Laiba; Shaheen, Hafsa; Sajid, Syeda Azka; Yasin, Razia (Indonesian Journal of Agriculture and Environmental Analytics, 2024)
Aquaponics, a symbiotic integration of aquaculture and hydroponics, presents a promising approach to sustainable agriculture by maximizing resource utilization and minimizing environmental impact. This study explores recent innovations in aquaponics technology and the development of sustainable infrastructure to support its widespread adoption. A systematic literature review is conducted, showing the fundamentals of aquaponics and its key components such as fish tanks, grow beds, and biological filters. Innovations in technology are examined, including advanced monitoring and control systems, integration of renewable energy sources, automation, and novel growing techniques. Sustainable infrastructure for aquaponics is analyzed, focusing on water management strategies, energy efficiency measures, material selection, and integration with urban agriculture. Furthermore, the alignment of aquaponics technology and sustainable infrastructure development with the United Nations Sustainable Development Goals (SDGs) is studied, particularly in achieving goals related to zero hunger, clean water and sanitation, responsible consumption and production, and climate action.